2008
DOI: 10.1038/ajh.2008.176
|View full text |Cite
|
Sign up to set email alerts
|

Can Validated Wrist Devices With Position Sensors Replace Arm Devices for Self-Home Blood Pressure Monitoring? A Randomized Crossover Trial Using Ambulatory Monitoring as Reference

Abstract: There might be important differences in HBP measured using validated wrist devices with position sensor vs. arm devices, and these could impact decisions relating to the patient in clinical practice. Measurements taken using arm devices are more closely related to ABP values than those recorded by wrist devices. More research is needed before recommending the widespread use of wrist monitors in clinical practice. American Journal of Hypertension doi:10.1038/ajh.2008.176American Journal of Hypertension (2008); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…The full text of 164 papers was reviewed for eligibility (figure 1) and 37 studies were included (32 published in English). One was a randomised trial and one a case–control study;17 18 the remainder were cross-sectional studies. Twenty studies (26 comparisons) had extractable data, all of which were of cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full text of 164 papers was reviewed for eligibility (figure 1) and 37 studies were included (32 published in English). One was a randomised trial and one a case–control study;17 18 the remainder were cross-sectional studies. Twenty studies (26 comparisons) had extractable data, all of which were of cross-sectional design.…”
Section: Resultsmentioning
confidence: 99%
“…17 21 23 31 Funnel plot and χ 2 tests suggested a low probability of publication bias (p=0.89) or heterogeneity (χ 2 : Q=4.26, df=2.00, p=0.06), and subgroup analyses were not possible.…”
Section: Resultsmentioning
confidence: 99%
“…The error introduced by the hydrostatic effect of differences in position of the wrist relative to the heart can be avoided with the use of position sensors. Indeed, it has been shown that wrist devices are more accurate if they are provided with optical sensors that guide the arm to an appropriate measuring position [17,18]. Another contrary view against the use of equipment performing measurement at the wrist is that wrist cuffs may insufficiently occlude the wrist arteries and thus yield higher BP readings.…”
Section: Discussionmentioning
confidence: 97%
“…Approximately two‐thirds of the facilities used upper arm BP measurement devices, indicating that use of these devices is sufficiently practical in these settings. Moreover, wrist devices, which have been reported to be inaccurate,11, 12 are not recommended by the guidelines 3. Guggiari and colleagues reported that relative to upper arm devices, validated wrist devices significantly underestimate BP in the elderly 13…”
Section: Discussionmentioning
confidence: 99%